Dual‐Channel Flexible Strain Sensors Based on Mechanofluorescent and Conductive Hydrogel Laminates. Issue 5 (7th January 2022) - Lin, Guoqing; Si, Muqing; Wang, Longgang; Wei, Shuxin; Lu, Wei; Liu, Hao; Zhang, Yi; Li, Danyang; Chen, Tao
Abstract: Flexible strain sensors are of great importance in many emerging applications for human motion monitoring, implanted devices, and human–machine interactive systems. However, the dual‐channel sensing systems that enable both strain‐dependent electronic and visually optical signal responses still remain underdeveloped, but such systems are of great interest for human–machine interactive uses. Here, inspired by the mechanically modulated skin color changes of squids via muscle contracting/releasing movements, a class of mechanofluorescent and conductive hydrogel laminates for visually flexible electronics is presented. The sensing laminates consist of interfacially bonded red fluorescent hydrogel, polydimethylsiloxane and carbon nanotubes (CNTs) film. Since the densely stacked microscopic CNTs film can be precisely stretched to induce the formation of network microcracks, the developed hydrogel laminates are endowed with simultaneous fluorescence‐color and resistance changes, which can function as dual‐channel flexible sensors for real‐time human motion monitoring. These properties make the bioinspired soft hydrogel laminate electronics quite promising in the flexible electronics field. Abstract : Inspired by the mechanically modulated skin color changes of squids via muscle contracting/releasing movements, a powerful kind of mechanofluorescent and conductive hydrogel laminates is developed. The materials have the properties of the desirable strain‐dependent continuous and synergistic optical/electronic signal changes. They can be used as dual‐channel conformal biomimetic soft sensing skins for real‐time human motion monitoring.